Experiencing textures: the materiality of illegitimacy in Wilkie Collins's No Name. (2nd January 2022) - Hartl, Anja
ABSTRACT: This article introduces texture as a key category of material analysis in Victorian literature and culture. Challenging distinctions between inside and outside structures, texture offers not only a complex, multi-layered understanding of material surfaces but also provides aesthetic and interpretive tools for rendering and analysing matter in literary and cultural representations. Drawing on Wilkie Collins's No Name, this article argues that the novel presents the protagonist's illegitimacy as a material condition by foregrounding the textural qualities of her bodily surface. Textural principles serve as a central technique of characterisation in No Name and are a crucial device through which the characters shape themselves and assess each other. As a means of interrogating Victorian laws and norms, the novel uses textures to show how normative conceptions of (il)legitimacy inform the characters' and the narrator's perception of (bodily) matter. The article shows how the novel's textural construction of bodily materiality undermines comfortable distinctions between inside and outside, subject and object, as well as legitimate and illegitimate.